Effect of surface chemistry of Fe-Ni nanoparticles on mechanistic pathways of azo dye degradation - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Environmental Science & Technology, 2007)
The degradation of Orange G a monoazo dye, in aqueous solutions was investigated using as-synthesized and stored Fe-Ni bimetallic nanoparticles. Batch experiments with a nanocatalyst loading of 3 g/L showed complete. dye degradation (150 mg/L) after 10 min of reactiontime. HPLC-MS analysis of the degradation products showed that assynthesized nanoparticles reductively cleaved the azo linkage to produce aniline as the major degradation product. However, 1-year-stored nanoparticles showed an oxidative degradation of Orange G through a hydroxyl-radical induced coupling of parent and/or product molecules. XPS analysis in corroboration with HPLC-MS data showed that the surface chemistry between Fe and Ni in assynthesized and stored nanoparticles play a crucial role. in directing the mode of degradation. Reductive dye degradation using as-synthesized nanoparticles proceeded through hydride transfer from nickel, whereas formation of a Fe (2+) -Ni(0) galvanic cell in stored nanoparticles generated hydroxyl radicals from water in a nonFenton type reaction. The latter were responsible for the generation of radical centers on the dye molecule, which led to a coupling-mediated oxidative degradation of Orange G. The generation of hydroxyl radicals is further substantiated with radical quenching experiments using ascorbic acid indicating that stored nanoparticles degrade Orange G through a predominantly oxidative mechanism. HPLC-MS and XPS analysis of dye degradation using as-synthesized nanoparticles exposed to air and water confirmed that the reductive or oxidative degradation capability of Fe-Ni nanoparticles is decided by the time and type of catalyst aging process.

Efficient synthesis of fused 1,2,3-triazolo-delta-lactams using huisgen [3+2] dipolar cycloaddition ``click-chemistry'' in water - Kumar, Indresh; Rode, Chandrashekhar V. (Chemistry Letters, 2007)
A general approach for the quick synthesis of various 1,2,3-triazolo-delta-lactams has been described, which involves the Huisgen [3 + 2] dipolar cycloaddition of azides derived from different amino acids with dimethyl acetylenedicarboxylate in water followed by cyclization.

Enhancement of glycerol conversion to acetol in high-temperature liquid water by high-pressure carbon dioxide - Yamaguchi, Aritomo; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2008)
Dehydration of glycerol to acetol proceeded in high-temperature liquid water at 573 K in a batch reactor. The acetol formation rate increased with an addition of high-pressure carbon dioxide.

Efficiency and recycling capability of montmorillonite supported Fe-Ni bimetallic nanocomposites towards hexavalent chromium remediation - Kadu, Brijesh S.; Sathe, Yogesh D.; Ingle, Abhijit B.; Chikate, Rajeev C.; Patil, Kashinath R.; Rode, Chandrashekhar V. (Applied Catalysis B-Environmental, 2011)
The remediation of Cr(VI) from simulated water streams is investigated using Fe-Ni bimetallic nanoparticles (Fe-Ni NPs) and their nanocomposites prepared with montmorillonite (MMT) clay. These nanocomposites are characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) surface area analyses. XRD analysis revealed proper dispersion as well as intercalation of Fe-Ni NPs in the clay matrix. TEM of nanocomposites showed the presence of spherical particles having a size of 20-40 nm. Batch experiments with a 25 mg L(-1) Cr(VI) solution and 2 g L-1 Fe-Ni NPs exhibited complete reduction of Cr(VI) within 10 min that follows first order reaction kinetics. Amongst 25%, 50%, 75% in situ and loaded nanocomposites, 75% compositions possess better activity with enhanced reduction capacity below pH 4 due to generation of reactive H center dot species. XPS analysis of nanocomposites after Cr(VI) treatment suggested that reduction process occurs through Cr(111) formation followed by its subsequent reduction to Cr(0). Their potentiality towards reusage is established from the recycling experiments that revealed the order of efficiency as 75% in situ > Fe-Ni NPs > 75% loaded nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cr(VI) remediation; Iron-nickel bimetallics; Montmorillonite; Nanocomposites; Recycling

Effect of carbon dioxide pressure on 4-t-butylphenol hydrogenation activity of supported rhodium catalyst - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of the Japan Petroleum Institute, 2013)
Hydrogenation of 4-t-butylphenol over an activated carbon-supported rhodium catalyst in carbon dioxide solvent was analyzed based on phase observation with a view cell and calculations of the solubility of 4-t-butylphenol using the Peng-Robinson equation of state as a function of carbon dioxide pressure. The reaction experiments showed that the initial reaction rate of 4-t-butylphenol at 313 K under 2 MPa of hydrogen pressure was increased by the addition of carbon dioxide, especially above a total pressure of 11 MPa. Direct visual observation showed that the solubility of 4-t-butylphenol increased with higher carbon dioxide pressure. The calculations based on the Peng-Robinson equation of state also showed that the solubility of 4-t-butylphenol in the 4-t-butylphenol carbon dioxide hydrogen (2 MPa) system at 313 K significantly increased by addition of carbon dioxide above a total pressure of 11 MPa. We concluded that the increase in the hydrogenation rates was caused by the increased concentration of 4-t-butylphenol substrate in the carbon dioxide solvent.
Keywords: 4-t-Butylphenol hydrogenation; Carbon dioxide solvent; Peng-Robinson equation; Rhodium catalyst; Supercritical fluid

Effect of composition and pretreatment parameters on activity and stability of Cu-Al catalysts for water-gas shift reaction - Mane, Rasika B.; Jeong, Dae-Woon; Malawadkar, Atul V.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (ChemCatChem, 2014)
We investigated various Cu species responsible for highly efficient Cu-Al oxide catalyst for the water-gas shift reaction (WGSR). The formation of various Cu species was achieved by systematically varying the Cu-Al composition in the coprecipitated mixed Cu-Al oxides. The Cu-Al composition of 70:30 (Cu-Al-7) was the best for WGSR using the reformate gas composition. In addition, the Cu-Al-7 catalyst reduced under 100% H-2, was relatively stable with time on stream of 100 h, at higher gas hourly space velocity of 36201 h(-1). The structural investigation of our coprecipitated catalysts with varying Cu-Al compositions revealed the formation of nonzero oxidation state copper and metallic Cu to be essential for the observed WGSR activity. In addition, the highest activity and stability of Cu-Al-7 catalysts reduced under 100% H-2 at lower temperature was attributed to particle-size stabilization and a lower extent of Cu aggregation by Cu2O and boehmite phases, respectively, along with the formation of various Cu species during the activation protocol for 12 h. Complete CO2 selectivity without methanation was observed for all the Cu-Al compositions irrespective of their pretreatment conditions.
Keywords: aluminum; Copper; fuel cells; Hydrogen; reduction

Efficient palladium catalyzed Mizoroki-Heck cross-coupling in water - Jadhav, Sanjay N.; Rode, Chandrashekhar V. (Green Chemistry, 2017)
The homogeneous Pd-catalysed Mizoroki-Heck coupling reaction was successfully performed in water in the absence of any additives under aerobic conditions. The various key reaction parameters that affect the yield of the desired cross-coupling product were optimized. The Pd(PPh3)(4)/Et3N/H2O/98 degrees C catalyst system was found to be highly active (TOF = 12 to 14 h(-1)) towards achieving excellent yield of the Mizoroki-Heck coupling products for a wide range of electron-withdrawing as well as electron-donating aryl bromides and chlorides in the shortest reaction time. Pd(PPh3) 4 catalyst deactivation during the Mizoroki-Heck coupling reaction was investigated and to evolve a strategy for achieving ten times Pd-metal recyclability without appreciable loss of its activity. Thus, the proposed mechanism provides access to a variety of olefins in aqueous medium, making this protocol eco-friendly.

Effect of alkali and alkaline earth metal on Co/CeO2 catalyst for the water gas shift reaction of waste derived synthesis gas - Lee, Yeol-Lim; Jha, Ajay; Jang, Won-Jun; Shim, Jae-Oh; Rode, Chandrashekhar V.; Jeon, Byong-Hun; Bae, Jong Wook; Roh, Hyun-Seog (Applied Catalysis A-General, 2018)
We prepared a series of alkali (Na and K) and alkaline earth metal (Ca and Ba) promoted Co/CeO2 catalysts to investigate the effect of the promoter on the catalytic performance of the catalyst in the high-temperature water gas shift (WGS) reaction of waste derived synthesis gas. Interestingly, alkali metal promoted catalysts deactivated rapidly compared to alkaline earth metal promoted catalysts. Alkaline earth metal promoted catalysts showed relatively higher stability (>50 h) even at a very high gas hourly space velocity of 143,000 h(-1). X-ray diffraction (XRD) and transmission electron microscopy (TEM) results reveal that the higher stability of the alkaline earth metal promoted catalysts was due to the strong resistance to sintering, showing a relatively small crystallite size of metallic cobalt compared to the alkali metal promoted catalysts after WGS reaction.
Keywords: Alkaline earth metal; Co/CeO2; High temperature water-gas shift; Sintering resistance; stability; Waste derived synthesis gas

Effect of titration time on the catalytic performance of Cu/CeO2 catalysts for water-gas shift reaction - Na, Hyun-Suk; Shim, Jae-Oh; Jang, Won-Jun; Jeon, Kyung-Won; Kim, Hak-Min; Lee, Yeol-Lim; Lee, Da-We; Yoo, Seong-Yeun; Bae, Jong Wook; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Today, 2018)
We herein report the preparation of ceria (CeO2) via a simple precipitation method for use as a catalyst support in the water-gas shift (WGS) reaction. More specifically, we optimized the titration time required to obtain highly active CeO2-supported catalysts for the WGS reaction. As such, Cu was employed as the active metal coupled with the CeO2 support. Notably, the CeO2-0 supported Cu catalyst (where the precipitant was immediately injected into a cerium nitrate solution) exhibited the highest CO conversion at a gas hourly space velocity of 36,050 h(-1). This high catalytic activity of the Cu/CeO2-0 catalyst was mainly due to its high Brunauer-Emmett-Teller (BET) surface area, enhanced Cu dispersion, high number of oxygen vacancies, and enhanced reducibility.

Efficient and convenient heterogeneous Cu/MCM-41 catalyst for the synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives - Dhengale, Shankar D.; Bhosale, Tanaji R.; Shinde, Sachin B.; Rode, Chandrashekhar V.; Kolekar, Govind B.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2023)
An efficient and convenient method for synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives using Cu/MCM-41 (20 mg) as heterogeneous catalyst. The advantages have an excellent product yield within a short time and easy work-up procedure, and the products have directly recrystallized from hot methanol with cost-effective catalyst. One-pot three-component reaction from aromatic aldehydes, cyclic 1,3-dicarbonyl compounds, and 1-naphthyl amine has been carried under ethanol as a solvent with reflux condition. Moreover, the catalyst can be recovered conveniently and reused efficiently, and recyclable. [GRAPHICS] .
Keywords: Benzo[c]acridine; dimedone; Heterogeneous Cu/MCM-41 catalyst; Multicomponent one-pot reaction

Etherification of biomass-derived glycerol to oxygenated fuel additives using dodecatungstophosphoric-silica-supported catalyst: characterization and kinetic studies - Magar, Subhash B.; Kapoor, Ashish; Jana, Sumit Kumar; Pal, Dan Bahadur; Rode, Chandrashekhar V. (Biomass Conversion and Biorefinery, 2023)
Commercial biodiesel production is becoming popular due to its sustainability and reduced greenhouse gas emissions in comparison to fossil fuels. Biodiesel production involves the co-generation of crude glycerol that is not directly viable. Valorization of glycerol is essential from techno-economic perspective to achieve goals of circular economy. In this study, the glycerol etherification was carried out using tert-butyl alcohol in presence of dodecatungstophosphoric/silica (DTP/SiO2) catalyst for production of tert-butyl glycerol ethers that can be used as fuel additives. A series of DTP/SiO2 catalysts were prepared with various compositions by impregnating heteropoly acids (HPA, H3PW12O40). The product analysis was performed to monitor mono-, di-, and tri-tert-butyl glycerol ethers. The kinetic studies were conducted based on Langmuir-Hinshelwood model. The rate constants were determined from experimental data by regression analysis. The catalysts were characterized by X-ray diffraction, SEM/EDX, and thermogravimetric analysis. Varying DTP loadings resulted in different catalytic activities. Activation energy (38.23 kJ/mol), activation enthalpy (25.94 kJ/mol), activation entropy (-163.8 J/mol/K), and Gibbs free energy of activation (88.67 kJ/mol) were attained for DTP/SiO2 (20%) catalyst that exhibited the best selectivity for di-tert-butyl glycerol ethers.
Keywords: Catalytic; etherification; fuel additives; Hinselwood; Impregnation; kinetics; Langmuir